Pengaruh Hubungan Antara Profitabilitas, Pertumbuhan Penjualan, dan Struktur Aset Terhadap Struktur Modal - Christian Christian; Yanuar Yanuar (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of this study is to obtain empirical evidence about the effect of profitability, sales growth, and asset structure on firm capital structure in manufacturing companies listed at Indonesian Stock Exchange during the years 2011-2018. This study uses purposive sampling method to collect data and consists of 11 manufacturing companies listed at Indonesian Stock Exchange during the years 2011-2018. The hypothesis was tested by using multiple linear regression. The results of this study show that profitability has negative significant influence on firm capital structure, sales growth have negative significant influence on firm capital structure, asset structure have negative significant influence on firm capital structure, and also fluctuating exchange rate strengthen the relationship between profitability and firm capital structure.